The Influence of Augmented Reality Technology on Young Consumers’ Online Purchasing Decisions - Nguyen Thi Hoi (Universitas Airlangga, 2026)
Background: Augmented reality (AR) has emerged as a transformative technology in e-commerce, enabling immersive, interactive, and personalized shopping experiences that help bridge the gap between online and offline retail environments. Although the adoption of AR has gained increasing attention in digital commerce, empirical evidence regarding the determinants of AR-enabled purchasing behavior remains limited, particularly among young consumers in emerging digital economies. Objective: This study aims to examine the factors that influence AR-enabled online purchasing decisions and identify the technological, psychological, social, and behavioral drivers that encourage consumers to adopt AR-supported shopping experiences. The proposed framework is illustrated through a survey conducted among young consumers in Hanoi, Vietnam, to provide empirical evidence. Methods: An integrated research framework was developed based on the TRA, TPB, UTAUT2, and social impact models. We employed a quantitative approach using data collected from 400 respondents who had prior experience using AR features in online shopping. SEM was applied to test the proposed hypotheses and evaluate the relationships among the constructs. Results: The findings indicate that Habit, Belief, Satisfaction, Social Influence, Facilitating Conditions, Perceived Number of Users, Subjective Norms, Effort Expectancy, and Attitude significantly influence consumers’ behavioral intention and purchase decision. In addition, BI serves as a significant mediating mechanism through which AR adoption factors are translated into actual purchasing behavior. Conclusion: By providing a comprehensive framework for understanding consumer adoption of AR technologies in online shopping environments, this study contributes to the growing literature on AR-enabled commerce. The findings offer practical implications for e-commerce platforms, digital retailers, and technology providers seeking to enhance customer engagement, trust, and purchase conversion through AR-enabled shopping experiences. The empirical evidence from Vietnam further enriches the understanding of AR adoption in emerging digital markets while supporting the proposed framework’s broader applicability across e-commerce contexts. Keywords: Augmented Reality, online purchasing decisions, young consumers, behavioral intention, digital commerce